2023
DOI: 10.1590/1519-6984.250296
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Zingiber officinale effects on growth performance, immunity and gut morphology in broilers

Abstract: The current study aimed to determine the effects of different levels of Zingiber officinale as a herbal feed additive on growth performance, carcass characteristic, serum biochemistry, total bacterial count (TBC), gut morphology, and immunological parameters of broilers. A total of 1500, day-old broiler chicks (Hubbard) were equally accredited to five treatment groups, each with six replicates (50 birds/replicate). Five experimental diets were prepared using basal diet i.e. with antibiotics positive control (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…67 At the same time, current research confirmed that ginger has a positive impact on gut microbes of broilers. 68 In the study, the CE isolated from ginger oil was confirmed to perform excellent anti-inflammatory, immunomodulatory, and intestinal microenvironment regulation effects, which enriched the material basis of ginger to be further used as a food or drug for immunological diseases.…”
Section: Discussionmentioning
confidence: 88%
“…67 At the same time, current research confirmed that ginger has a positive impact on gut microbes of broilers. 68 In the study, the CE isolated from ginger oil was confirmed to perform excellent anti-inflammatory, immunomodulatory, and intestinal microenvironment regulation effects, which enriched the material basis of ginger to be further used as a food or drug for immunological diseases.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, a study conducted on pigs found that the addition of different dietary stevia doses elevated CFI and FCR (Xiong et al, 2022). Similarly, other authors reported that the addition of ginger to broiler diets increased CFI and FCR (Kafi et al, 2017;Safiullah et al, 2019;Asghar , 2021). The effect of ginger on performance is due to the fact that it contains two types of enzymes, i.e.…”
Section: Growth Performancementioning
confidence: 89%
“…The current study determined that the effect of heat stress and dietary SGE addition on cold carcass yield was significant, but cold carcass parameters were not affected. Similarly, another study showed that heat stress affected cold carcass yield (Habibian et al, 2016); however, other authors reported that the addition of herbal extract exerted no effect on cold carcass yield (Asghar et al, 2021;Kaplan and Köksal, 2021).…”
Section: Growth Performancementioning
confidence: 97%
“…While a wide variety of natural products, such as antioxidants, have shown promising results, many of the sources used may contain toxic and antinutritional factors and can have adverse effects when used in large quantities [ 4 , 11 ]. Natural and synthetic antioxidants that prevent lipid oxidation should be supplemented in the diet to sustain the quality of food products [ 12 , 13 ]. Therefore, further studies are needed to characterize the active compounds in these natural sources and evaluate their efficacy, safety, and stability in different amounts and different products.…”
Section: Introductionmentioning
confidence: 99%